REORIENTASI KEADILAN DALAM HUKUM KELUARGA ISLAM: GAGASAN KESETARAAN HAK SUAMI-ISTRI ERA KONTEMPORER - Rahman, Aidi; Nor Annisa Rahmatillah; ⁠Lisnawati (Mitsaqan Ghalizan, 2025)
This article examines the issue of unequal rights between husbands and wives in Islamic family law in Indonesia, particularly as reflected in the Compilation of Islamic Law (KHI) and the practice of religious courts. Although Islamic family law aims to promote harmony and justice within the household, several provisions still reflect patriarchal biases that disadvantage women, including the doctrine of wifely obedience, unilateral divorce rights for husbands, and the legitimization of polygamy. In addition, the prevalence of unregistered marriages (nikah siri) and divorces conducted outside court procedures further weakens legal protection for women and children. Using a normative-analytical approach, this article argues that gender inequality in Islamic family law does not originate from the principles of Sharia itself, but from historical interpretations and patriarchal sociocultural structures embedded in legal norms. Therefore, reforming Islamic family law is necessary to ensure alignment with the objectives of maqāṣid al-sharī‘ah justice, public welfare, and the protection of human dignity. This article offers several reform strategies, including revising discriminatory articles of the KHI, strengthening marriage registration systems, improving gender-sensitive legal literacy, and increasing women’s participation in legislative and policy-making processes. Through these efforts, Islamic family law can develop into an egalitarian and contextually relevant system capable of advancing substantive justice in modern society.